Anemia And Sleep Patterns Among Adolescent Women In Surakarta City The Title Of The Article Is English - Dyah Krisnawati Satia Pratiwi; Anastya, Emma; Nahdiyah Karimah (Universitas STRADA Indonesia, 2024)
Background. Anemia, a condition in which the hemoglobin (Hb) level in the blood is lower than the normal value, disrupts the oxygen distribution process to all body tissues, disrupts sleep patterns, and has an impact on monoamine metabolism due to insufficient oxygen concentration in the blood. It is also a public issue that affects a country's health indicators. Method. The chi square test was employed for both univariate and bivariate data analysis in this cross-sectional, quantitative observational study with a sample size of 76 participants. Result. The study found a strong correlation between anemia and sleep habits in adolescent girls (p=0.046; α=0.05; CI=95%). Analysis. Disruption of monoamine metabolic activity in the brain which plays a role in sleep physiology and the occurrence of sleep disorders in someone with iron deficiency. Conclution. Adolescent girls who are anemic have shorter sleep durations (<8 hours).